Are NSAIDs Safe? Assessing the Risk-Benefit Profile of Nonsteroidal Anti-inflammatory Drug Use in Postoperative Pain Management. Issue 6 (June 2021) - Chang, Ray W.; Tompkins, Danielle M.; Cohn, Stephen M.
In this article, we review controversies in assessing the risk of serious adverse effects caused by administration of nonsteroidal anti-inflammatory drugs (NSAIDs). Our focus is upon NSAIDs used in short courses for the management of acute postoperative pain. In our review of the literature, we found that the risks of short-term NSAID use may be overemphasized. Specifically, that the likelihood of renal dysfunction, bleeding, nonunion of bone, gastric complications, and finally, cardiac dysfunction do not appear to be significantly increased when NSAIDs are used appropriately after surgery. The importance of this finding is that in light of the opioid epidemic, it is crucial to be aware of alternative analgesic options that are safe for postoperative pain control.